A prospective, randomized, double blind, placebo-controlled evaluation of the effects of eicosapentaenoic acid and docosahexaenoic acid on the clinical signs and erythrocyte membrane polyunsaturated fatty acid concentrations in dogs with osteoarthritis. (June 2016) - Mehler, Stephen J.; May, Lauren R.; King, Crystal; Harris, William S.; Shah, Zubin
Abstract: Background: Osteoarthritis (OA) in dogs is a prevalent and serious condition. The most common treatment for the clinical signs of OA in dogs is the administration of nonsteroidal antiiflammatory pharmaceuticals. Omega-3 ( n− 3) fatty acids have been shown to reduce the clinical signs of osteoarthritis in dogs. Objective: The primary goals of this study were 1) to determine the effects of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) on the clinical signs of OA in dogs, 2) to evaluate the effects of supplementation on the arachadonic acid (ARA)/ (EPA+DHA) algorithm and 3) to correlate alterations in the ARA/(EPA+DHA) with changes in the clinical signs of canine OA. Methods: Seventy-eight client owned dogs were enrolled in a prospective, randomized, double-blind, placebo controlled clinical trial. Dogs were randomized to placebo oil or triglyceride n-3 oil (providing an average dose of 69 mg EPA+DHA/kg/day). Orthopedic examinations and blood analyses were performed at baseline, day 42, and day 84. A single investigator confirmed a diagnosis of OA of the coxofemoral joints and/or stifle joints in all dogs. Results: Seventy-four dogs completed the trial. All clinical outcomes for measuring discomfort, lameness, and joint severity at day 84 and all blood metrics at day 42 and day 84 significantly ( p <0.05) improved compared with placebo. No major side effects were observed. Conclusion and clinical relevance: This study demonstrated that the daily supplementation of a dogs diet with EPA and DHA shifts the blood fatty acid concentrations correlating to relief of clinical signs associated with OA in dogs. Highlights: Osteoarthritis in dogs is a prevalent and serious condition. The most common treatment for the clinical signs of OA in dogs is the administration of nonsteroidal antiiflammatory pharmaceuticals. Omega-3 ( n −3) fatty acids have been shown to reduce the clinical signs of osteoarthritis in dogs. Seventy-eight client owned dogs were enrolled in a prospective, randomized, double-blind, placebo controlled clinical trial to evaluate the effect of EPA and DHA on the iFATS™, a novel algorithm evaluating ARA/(EPA+DHA) and on the clinical signs of osteoarthritis. This study demonstrated that the daily supplementation of a dogs diet with EPA and DHA significantly shifts the iFATS in a favorable direction and is correlated with the relief of clinical signs associated with osteoarthritis in dogs.